1996
DOI: 10.1002/pc.10621
|View full text |Cite
|
Sign up to set email alerts
|

An experimental and theoretical study of creep of a graphite/epoxy woven composite

Abstract: The creep behavior of woven fiber polymer composites has been investigated through both an experimental study and analytical modeling. In the modeling, the matrix is assumed to be a 4‐parameter model (a Maxwell‐Voigt combination) and the fibers to be elastic. The fiber undulation model developed by Ishikawa and Chou for elastic behavior of woven fiber composites has been extended to the viscoelastic system by the correspondence principle. This considers the longitudinal and transverse fibers separately. The we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…A single Maxwell or a single Kelvin-Voigt element cannot represent the transient and instantaneous response of polymers accurately. Hence, using a combination of the two elements is recommended [28][29][30][31]. The strain in a creep test of semi-conductive polymer composites, such as Linqstat which is used when fabricating a force sensor, tends towards a constant value after a longer period of time.…”
Section: E Modeling Creep Behaviormentioning
confidence: 99%
“…A single Maxwell or a single Kelvin-Voigt element cannot represent the transient and instantaneous response of polymers accurately. Hence, using a combination of the two elements is recommended [28][29][30][31]. The strain in a creep test of semi-conductive polymer composites, such as Linqstat which is used when fabricating a force sensor, tends towards a constant value after a longer period of time.…”
Section: E Modeling Creep Behaviormentioning
confidence: 99%
“…7,8 Viscoelastic moduli have also been obtained numerically through direct finite element analysis 9 assuming a uniform distribution of fibers. For woven composites, Govindarajan et al 10 and Shrotriya and Sottos 11 proposed analytical models based on simplified weave geometries, but the flexural deformation of the fiber tows was not accounted for and was believed to be the source of significant discrepancy between predicted and measured viscoelastic responses. Predictions were improved when two-dimensional 11 and three-dimensional 12 finite element based methods were utilized to incorporate the influence of weave geometry, but still did not match the experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…Pasricha et al 18,19 Govindrajan et al 23 showed that the approximation of the composite as a combination of fibre undulation and the 4-parameter model (Maxwell-Voigt combination) could be successfully used to predict the time-dependent behaviour of woven-fibre polymer composites. The matrix was modelled using the 4-parameter model and fibres were assumed to be elastic in the composite model.…”
mentioning
confidence: 99%